Direct observation and measurements of subglacial deformation in a tunnel beneath Wright Lower Glacier, Antarctica - Fitzsimons, Sean (Zenodo, 2023)
Photographs and video of a tunnel excavated in the margin of Wright Lower Glacier, Antarctica